Biomarkers for Pancreatic Neuroendocrine Neoplasms (PanNENs) Management—An Updated Review - Bocchini, Martine; Nicolini, Fabio; Severi, Stefano; Bongiovanni, Alberto; Ibrahim, Toni; Simonetti, Giorgia; Grassi, Ilaria; Mazza, Massimiliano (Frontiers in Oncology, 2020)
Pancreatic neuroendocrine tumours (PanNENs) are rare sporadic cancers or develop as part of hereditary syndromes. PanNENs can be both functioning and non-functioning based on whether they produce bioactive peptides. Some PanNENs are well differentiated while others – poorly. Symptoms, thus, depend on both oncological and hormonal causes. PanNEN diagnosis and treatment benefit from and in some instances are guided by biomarker monitoring. However, plasmatic monoanalytes are only suggestive of PanNEN pathological status and their positivity is typically followed by deepen diagnostic analyses through imaging techniques. There is a strong need for new biomarkers and follow-up modalities aimed to improve the outcome of PanNEN patients. Liquid biopsy follow-up, i.e. sequential analysis on tumour biomarkers in body fluids offers a great potential, that need to be substantiated by additional studies focusing on the specific markers and the timing of the analyses. This review provides the most updated panorama on PanNEN biomarkers.